The Role of Organic Carbon in Natural and Synthetic Oestrogens Sorption onto Soils - Edriyana, Abd Aziz; W. A., Wan Omar; Aznilnda, Zainodin; Islam, Mir Sujaul (IACSIT Press, 2016)
Among the compounds implicated as Environmental Endocrine Disruptors (EEDs), the most potent to alter the normal functions of the endocrine systems of organisms and humans are the natural and synthetic oestrogen. They are hydrophobic and ubiquitous and remain in the final effluents for the vast majority of sewage treatment plant. Land application of animal manures and sewage sludge as fertilizers has been reported to increase the amount of hormones in soil. However, the information on the factor that influences the occurrence of these compounds in this environmental compartment is limited. This study investigates the sorption affinity of these oestrogens on soils by determining its soil-water partition coefficient (Kd), sorption coefficient normalised to organic carbon (Koc) and octanol-water partition coefficient (Kow). In this study, different percentage of organic carbon was used. The results obtained shows that the Kow is a good predictor of sorption among contaminants as the affinity of oestrogens in soils is strongly dependent to their Kow values. This study also shows that the solid-water partition coefficient (Kd) of all oestrogens have good correlation to the organic carbon content. The calculated sorption coefficient normalised to organic carbon (Koc) indicate a strong association of all oestrogens with organic carbon. Therefore it is concluded that the organic carbon is pertinent to the sorption of oestrogens in soils.